Пробиотические потенции Aerococcus viridans на биомодели организма белых мышей - Бібен, Іван Андрійович; Biben, Ivan; Зажарський, Володимир Володимирович; Zazharskiy, Volodymyr; Zazharskyi, Vladymyr; Zazharskyi, Volodymyr; Zazharskiy, V.; Zazharskyi, V.; Zazharskiy, Vladymyr; Сосницька, Альона Олександрівна; Sosnyts`ka, Alyona; Колосова, Вероніка Сергіївна; et al. (Інститут ветеринарної медицини НААН, 2018)
Для эффективного применения биопрепаратов на основе прокариот-пробиотиков, необходимо глубокое изучение их пробиотических потенций, механизмов конкурентного взаимодействия с представителями резидентной и транзиторной микрофлоры. Для выяснения этих вопросов были изучены на биомодели организма белых мышей наличие и количественная характеристика аэрококков в содержимом и гомогенате различных отделов желудочно-кишечного тракта. В результате проведенных экспериментальных работ установили, что аэрококки-антагонисты обитают во всех отделах пищеварительного тракта. Частота их обнаружения находилась в коррелятивной зависимости от содержания антагонистов в том или ином отделе кишечника. В наибольшем количестве аэрококки регистрировались в толстом отделе кишечника. Пробиотические прокариоты Aerococcus viridans являсь представителями индигенной микрофлоры, заселяют все открытые полости макроорганизма, при этом средний титр в кишечнике составляет 105 – 108 КОЕ/см3. При искусственной пероральной интродукции пробиотической культуры Aerococcus viridans прокариоты адгезируются во всех отделах желудочно-кишечного тракта, но наиболее интенсивно этот процесс происходит в тонком отделе кишечника, где аэрококки занимают свободные экологические ниши слизистой оболочки, вытесняя при этом пристеночную транзиторную микрофлору. Колонизационная резистентность кишечника обеспечивается слоем приэпителиальной слизи, секреторными Ig A, индигенной микрофлорой и ее метаболитами и является эффективным протективно-компенсаторным неспецифическим биомеханизмом, не допускающим контакт адгезинов патогенных микроорганизмов с рецепторным полем эпителиальных клеток организма-хозяина. В гомогенатах всех исследованных отделов кишечника аэрококки содержались в достаточно большом количестве, что косвенно свидетельствует о прочной связи антагонистов со слизистой оболочкой желудочно-кишечного тракта. Таким образом, можно утверждать, что аэрококки обладают способностью прикрепляться и колонизировать поверхность слизистой оболочки кишечника, занимая свои экологические ниши обитания и тем самым, вследствии конкурентного антагонизма за биотоп, препятствуют адгезии тразиторных патогенных и условно-патогенных энтеробактерий, что в целом характеризует аэрококки как микробионты обладающие выраженными пробиотическими потенциями. Для ефективного застосування пробіотичних препаратів необхідно глибоке вивчення їх пробіотичнких потенцій, механізмів конкурентної взаємодії з представниками резидентної и транзиторної мікрофлори. Для з’ясування цих питань були вивчені на біомоделі организму білих мишей наявність и кількісна характеристика аерококів у вмісту і гомогенаті різних відділів шлунково-кишкового тракту. В результаті проведених експериментальних робіт встановили, що аерококи-антагоністи мешкають в усіх відділах шлункового тракту. Частота їх виявлення знаходилась в корелятивній залежності від наявності антагоністів у тому чи іншому відділі кишечнику. В найбільшій кількості аерококи реєстувались у товтому відділі кишечнику. Враховуючи, що пробіотичні прокаріоти Aerococcus viridans є представниками індигенної мікрофлори, вони заселяють всі відкриті порожнини макроорганізму, при цьому середній титр складає 105 – 108 КОЕ/см3. При штучній пероральній інтродукції пробіотичної культури Aerococcus viridans прокаріоти адгезуются в усех відділах шлунково-кишкового тракту, але більш інтенсивно цей процес проходить в тонкому відділі кишечнику, де аерококи займають вільні екологічні ніші слизової оболонки, витісняючи при цьому пристінкову транзиторну мікрофлору. Колонізаційна резистентність кишечнику забезпечується шаром приепітелиального слизу, секреторними Ig A, індигенною мікрофлорою та її метаболітами і є еффективним протективно-компенсаторним неспецифічним біомеханизмом, не допускаючим контакт адгезинів патогенних мікроорганізмів з рецепторним полем епітеліальних клітин организму-хазяїна. В гомогенатах усіх досліджених відділів кишечнику аерококи містились у достатньо великій кількості, що опосередковано свідчить про міцний зв’язок антагоністів зі слизовою оболонкою шлунково-кишкового тракту. Таким чином, можливо стверджувати, що аерококи володіють здатністю прикріплятися і колонізувати поверхню слизової оболонки кишечнику, займаючи свої екологічні ніші мешкання і тим самим, внаслідок конкурентного антагонізму за біотоп, перешкоджають адгезії транзиторних патогенних и умовно-патогенних ентеробактерій, що в цілому характеризує аерококи як мікробіонти, що володіють вираженними пробіотичними потенціями. Introduction. Aerococcus viridans is an ubiquitous resident representative of the normal microbiocenosis of open cavities in animals and humans, an indicator of the health status of the macroorganism in relation to the quantitative and qualitative composition of the microbial community, primarily the intestinal tube. Aerococci belong to the active products of hydrogen peroxide and, possessing pronounced probiotic potencies, are able to enter into a competitive antagonistic relationship with the transient microflora for the ecological niche in the macroorganism, in this case, the surface of the mucosa of open cavities. Possessing an active colonizing abilities and a high adhesive activity, aerococci determine the composition of the microbiocenosis of the mucous membranes, preventing the colonization of mucous surfaces by transient microorganisms with pathogenic potencies. For the effective use of probiotic drugs, an in-depth study of their probiotic potencies, mechanisms of competitive interaction with representatives of resident and transitory microflora is necessary. To clarify these issues, the presence and quantitative characteristics of aerococci in the contents and homogenate of various parts of the gastrointestinal tract were studied on the biological model of the organism of white mice. The goal of the work. As a result of the experimental work, it was established that aerococci-antagonists live in all parts of the digestive tract. The frequency of their detection was correlative depending on the content of antagonists in this or that part of the intestine. In the largest number of aerococci were recorded in the large intestine. Taking into account that the probiotic prokaryotes of Aerococcus viridans are representatives of the indigenous microflora, they populate all open cavities of the macroorganism, with an average titer of 105 – 108 CFU/см3. With the artificial oral introduction of the probiotic culture of Aerococcus viridans, prokaryotes adhere in all parts of the gastrointestinal tract, but this process occurs most intensively in the small intestine, where aerococci occupy free ecological niches of the mucous membrane, displacing the wall transient microflora. Colonization resistance of the intestine is provided by a layer of epithelial mucus, secretory Ig A, indigenous microflora and its metabolites, and is an effective protective-compensatory nonspecific biomechanism that does not allow contact of the adhesions of pathogenic microorganisms with the receptive field of epithelial cells of the host organism. Results and Discussion. In the homogenates of all examined parts of the intestine, the aerococci were contained in a sufficiently large amount, which indirectly indicates a strong association of the antagonists with the mucosa of the gastrointestinal tract. Conclusions and perspectives of further research. Thus, it can be argued that aerococci have the ability to attach and colonize the surface of the intestinal mucosa, occupying their ecological niches and thus, due to competitive antagonism over the biotope, interfere with the adhesion of tracer pathogenic and opportunistic enterobacterias, which generally characterizes aerococci as microbionts possessing pronounced probiotic potencies.
Пробіотичні потенції Aerococcus viridans на біомоделі організму білих мишей
Probiotic potency Aerococcus viridans on biomodel of white mice organism
Keywords: білі миші; white mice; пробіотичні потенції; probiotic potency; адгезивні властивості; adhesive properties; колонізаційна властивість; colonization ability; конкурентний антагонізм; competitive antagonism